2015
DOI: 10.1016/j.antiviral.2015.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Ebola virus dynamics in mice treated with favipiravir

Abstract: The polymerase inhibitor favipiravir is a candidate for the treatment of Ebola virus disease. Here, we designed a mathematical model to characterize the viral dynamics in 20 mice experimentally infected with Ebola virus, which were either left untreated or treated with favipiravir at 6 or 8days post infection. This approach provided estimates of kinetic parameters of Ebola virus reproduction, such as the half-life of productively infected cells, of about 6h, and the basic reproductive number which indicates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 23 publications
2
58
2
Order By: Relevance
“…More generally, the exposure-response relationship cannot be anticipated, and a PK-virus dynamic analysis, as proposed, for instance, for mice infected with EBOV (35), will be needed to fully characterize the antiviral activity of favipiravir. In this respect, viral dynamic modeling teaches that the time of treatment initiation is critical to reduce virus levels and that a drug affecting viral replication, such as favipiravir, will have only a very limited impact on viremia if it is administered after peak viremia (35). Furthermore, the duration of treatment may also be critical, as previous studies showed that EBOV-infected macaques treated with BCX4430 or ZMapp may still have detectable viremia at 14 days postchallenge (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, the exposure-response relationship cannot be anticipated, and a PK-virus dynamic analysis, as proposed, for instance, for mice infected with EBOV (35), will be needed to fully characterize the antiviral activity of favipiravir. In this respect, viral dynamic modeling teaches that the time of treatment initiation is critical to reduce virus levels and that a drug affecting viral replication, such as favipiravir, will have only a very limited impact on viremia if it is administered after peak viremia (35). Furthermore, the duration of treatment may also be critical, as previous studies showed that EBOV-infected macaques treated with BCX4430 or ZMapp may still have detectable viremia at 14 days postchallenge (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few of these compounds have shown protection in animal models of EBOV, which is a critical step for screening potential drug candidates for future human clinical trials (3,5,6). One class of compounds that has emerged with many promising antiviral candidates is the group of flavonoid molecules.…”
mentioning
confidence: 99%
“…The primary outcome (Box 1) was mortality within a period of 14 days. Doses in adults were determined based on results from mouse studies [30], as well as on pharmacokinetic simulation and dosage tests in humans [28]. …”
Section: Small Molecule Inhibitors: Direct Intracellular Inhibition Omentioning
confidence: 99%